Graphene‐based dual‐band antenna in the millimeter‐wave band. Issue 12 (9th October 2018) - Luo, Yanbin; Yan, Xin; Zeng, Qingsheng; Zhang, Jinnan; Zhang, Xia; Li, Bang; Lu, Qichao; Ren, Xiaomin
Abstract: A graphene‐based dual‐band millimeter‐wave antenna is demonstrated. The antenna is fabricated on a high‐resistivity Si substrate covered with SiO2 . A monolayer graphene is transferred onto the SiO2 and acts as the antenna radiator. The antenna works at 28.1 GHz and 37.4 GHz, with return loss less than −10 dB. By applying DC bias, the return loss at the two bands exhibits regular variations. The change mechanism of the return loss is also analyzed. Particularly, this work approves the potential of the graphene in the millimeter‐wave band by theory and experiments, which could advance graphene for real world applications.